Perceptions of the usefulness of external support to immunization coverage in Guinea-Bissau: a Delphi analysis of the GAVI-Alliance cash-based support. - Ferrinho, Paulo de Lyz Girou Martins (2021)
INTRODUCTION Although many countries have improved vaccination coverage in recent years, some, including Guinea-Bissau, failed to meet expected targets. This paper tries to understand the main barriers to better vaccination coverage in the context of the GAVI-Alliance (The Global Alliance for Vaccines and Immunisation) cash-based support provided to Guinea-Bissau. METHODS The analysis is based on a document analysis and a three round Delphi study with a final consensus meeting. RESULTS Consensus attributed about 25% of the failure to perform better to implementation problems; and about 10% to governance and also 10% to scarce resources. The qualitative analysis validates the importance of implementation issues and upgraded the relevance of the human resources crisis as an important drawback. The recommendations were balanced in their upstream-downstream focus but were blind to health information issues and logistical difficulties. CONCLUSIONS It is commendable that such a fragile state, with all sorts of barriers, manages to sustain a slow steady growth of its vaccination coverage. Not reaching the targets set reflects the inappropriateness of those targets rather than a lack of commitment of the health workforce. In the unstable context of countries such as Guinea-Bissau, the predictability of the funds from global health initiatives like the GAVI-Alliance seem to make all the difference in achieving small consistent health gains even in the presence of other major bottlenecks.